Satellite Image Based Mapping of Wetland Tundra Landscapes Using ILWIS GIS - Lemenkova Polina (Zenodo, 2015)
The aim of the work is the analysis of the distribution of different types of the landscapes in the wetland tundra of the Yamal Peninsula. The Yamal Peninsula is important biogeographic region of the Arctic. It is located in the subarctic continental climate zone and crosses two main physical and geographical regions: subarctic and Arctic tundra. The geomorphological feature of Yamal consists in almost flat plain surface. This creates favourable conditions for the formation of a dense network of interconnected small lakes and shallow rivers and wetlands. The wetland areas, swamps and areas with high moist soil dominating in this area are subject to regular annual seasonal flooding, in particular in spring. Current work reports monitoring of the changes in land cover types of tundra landscapes for 2 decades (1988-2011). Technically, the analysis of landscape dynamics was performed by Landsat TM satellite images for 1988 and 2011. The originality of the work lies in the application of ILWIS GIS software for the spatial analysis and processing of space on the Bovanenkovo region, Yamal, Russia. P. Lemenkova. "Satellite Image Based Mapping of Wetland Tundra Landscapes Using ILWIS GIS". Russian. In: Actual Problems of the State and Management of Water Resources. Proceedings of the International Conference (Volga State University of Technology, Mar. 19, 2015). Ed. by A. V. Kusakin and T. N. Efimova. Yoshkar-Ola, Russia: VolgaTech Press, 2015, pp. 110–113. isbn: 978-5-9903856-9-6. doi:10.6084/m9.figshare.7435520. url: https: //elibrary.ru/item.asp?id=24613025.